(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Transportation is the physical activity of moving goods or passengers from one place to another, which has a significant role in economic, social, cultural, and political development. With transportation, the distribution of these goods and production results can be carried out and reach all regions evenly, ultimately increasing regional and national income, opening up isolated areas, and increasing revenue for the local region and the country in general. The increasing interaction of transportation between economic and social activities in an area causes the need for a beneficial transportation role to assist movement in that area. A region’s economic and social development is also strongly influenced by the transportation system, which will ultimately increase the region’s growth. The success of the development of a part is strongly influenced by the role of transportation as the lifeblood of an area, including political, economic, social and cultural life as well as defense and security. To realize the mission championed by transportation, namely to improve the quality of services and management of transportation services that are reliable, competitive and provide added value that can support the recovery of the national economy, especially in the field of River Lake and Crossing Transportation (ASDP), the port as one of the transportation nodes is considered it is necessary to improve the quality and quantity as well as performance in serving port service users. Simanindo Port, located in Samosir Regency, North Sumatra Province, is a commercial port managed by the Department of Transportation which serves public services to carry out crossing activities that connect the Simanindo Port in Samosir Regency with Tigaras Port in the Simalungun Regency area.